The use of synthesized zeolites from power plant rice husk ash obtained from Thailand as adsorbent for cadmium contamination removal from zinc mining. Issue 3 (September 2015) - Santasnachok, Chawikarn; Kurniawan, Winarto; Hinode, Hirofumi
Abstract: The people from the 12 villages near the zinc mining in Mae Sot District, Tak Province, and Northwest of Thailand, were suffering contamination with cadmium (Cd 2+ ). It was released into the main source of water supply, Mae Taw River, which also be used for agriculture. This represents a serious problem that should be addressed accordingly. This study aims to investigate the synthesized zeolite from agriculture waste by-product in Thailand such as; rice husk ash (RHA) with white part is containing high silica content which can be used as a potential zeolites precursor and used to solve the problem by removing cadmium in aqueous solution via batch experiments. The removal of Cd 2+ in the concentration range of 50–500 mg/L. The maximum removal capacity of synthesized zeolite Na−A and Na−X for Cd 2+ were found to be 736.38 and 684.46 mg/g, respectively. The result was compared to synthetic zeolite 3A commercial shown that synthesized zeolites from RHA have high removal capacity close to commercial one of 753.58 mg/g using 0.3 g/L dosage of zeolite and consistent with an endothermic reaction, an increase in the temperature (20–40 °C) resulted in increasing cadmium adsorption rate. Therefore, the synthesized zeolites from RHA have high potential to remove cadmium contamination in water.